IMPLEMENTATION OF EIDETIC MEMORY METHODS DURING TEACHING UKRAINIAN AS A FOREIGN LANGUAGE - Леся Назаревич (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2015)
Actuality of studying methods of teaching Ukrainian as a foreign language is emphasized. Accent is made on effectiveness of Eidetic memory as a way of teaching Ukrainian as a foreign language. Some methods of Eidetic memory (string, pictographic, phonetic associations) are analyzed and illustrated. The basic Eidetic memory principle - visibility which is based on the development of creative thinking and serves as a tool for fast and effective studying of new material. On the basis of practical experience it is proved that the methods viewed make the work with foreign students more effective.